PLAY-BASED LEARNING FOR CREATING FUN LANGUAGE CLASSROOM - Suwastini, Ni Komang Arie; Puspawati, Ni Wayan Nilam; Nitiasih, Putu Kerti; Adnyani, Ni Luh Putu Sri; Rusnalasari, Zulidyana Dwi (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
Playing is essential for children. Thus, play-based learning has been argued to create engaging learning. Employing literature review research from George, this study aims to provide a comprehensive review of play-based learning, the types of play-based learning, and their strengths and weaknesses for language learning. The data sources were previous studies published from 2015-2020 in reputable international journals and accredited national journals indexed by Sinta and other relevant sources. Play-based learning can be categorized into three types: child-directed play that results in involuntary creative learning; teacher-directed play, which allows teachers to set up more structured plays; and mutually-directed play, which combines both types of play to provide maximum benefits for both teachers and children. It implies that teachers should select the type of play that suits the children's needs, situation, and learning objectives when choosing to implement play-based learning. Abstrak: Bermain sangat penting bagi anak-anak sehingga pembelajaran berbasis bermain dianggap sebagai pembelajaran yang menarik. Dengan menerapkan model Kajian Pustaka dari George, penelitian ini bertujuan untuk menyajikan paparan komprehensif mengenai pembelajaran berbasis permainan, jenis-jenisnya, serta keunggulan dan kelemahannya untuk pembelajaran bahasa. Sumber data dalam penelitian ini adalah hasil penelitian-penelitian yang diterbitkan pada 2014-2020 di jurnal internasional bereputasi atau jurnal nasional terakreditasi Sinta, serta sumber lain yang relevan. Pembelajaran berbasis permainan dapat dikelompokkan menjadi tiga jenis. Pertama, permainan bebas yang diarahkan anak-anak, yang menghasilkan pembelajaran bahasa spontan dan kreatif tanpa campur tangan guru. Kedua, permainan yang diarahkan guru, yang memungkinkan pembelajaran yang lebih terstruktur dengan arahan guru. Ketiga, permainan kolaborasi yang memberikan manfaat yang maksimal karena baik guru maupun anak-anak merencanakan permainan tersebut. Bagaimanapun, dalam memilih jenis permainan yang akan digunakan, guru diharapkan mempertimbangkan kekuatan dan keterbatasan masing-masing jenis permainan berdasarkan kebutuhan, situasi, dan tujuan pembelajaran anak.